Severe Obstetric Morbidity: Prevalence, Risk Factors and Outcome - Reena RP; Umadevi N; Ajitha BK (National Journal of Community Medicine, 2015)
Background: Severe Obstetric Morbidity (SOM) can be a supple- mentary indicator to maternal mortality. We have very little in- formation about its prevalence and risk factors. Methods: A cross sectional study using a nested case control study design was done to estimate the prevalence and factors as- sociated with SOM. Women delivering at a public run tertiary care facility were screened and cases meeting the criteria for SOM were compared with a control group . The maternal and fetal out- come were analyzed. Results: The prevalence rate of SOM was 34.3 per 1000 deliveries. Hypertensive disorders and its complications were common causes. Exposure to poverty, undesirable maternal and perinatal outcomes were more frequent among cases than controls Conclusions: .A significant proportion of women with SOM had to bear the dual burden of poverty and serious illness during pregnancy. Early detection and appropriate management of SOM can reduce the incidence and severity of morbidity.